High Non-Linear Fiber Length Verification in Optical Regeneration using Non-Return Zero and Return Zero Signal - Fatin Nabilah, Mohamad Salleh; Nor Shahida , Mohd Shah; Nurul Nadia , Shamsuddin; Siti Nurul Sharina , Mat Yaacob (Universiti Malaysia Pahang, 2016)
In this paper, the effect of high nonlinear fiber length in optical regeneration are investigated. To address the goal of this paper, there are two part need to fulfilled which are input pulse part and regeneration part. This work is focus on simulation by using OptiSystem Software. The simulated results show that the effective length for NRZ signal are starting from 0.5km to 2km while for RZ signal are 0.5km to 1km that suitable for optical regeneration. The comparisons of Max Q-factor and Min. log of BER for different signals are recorded.